Effect of Soaking Time on the Mechanical Properties of Kenaf/Epoxy Composites - Muiz bin Saringon, Abdul; Kalam, Anizah; Md Yusof, Fauziah; Ahmad Shafiq Shauqi Syed Mohamed, Syed (International Journal of Engineering and Technology, 2018)
Mechanical properties of Kenaf/Epoxy composites are depended on the bonding between fibers and matrix.  Fiber treatment is one of the methods to improve the fibre/matrix bonding and subsequently enhances their mechanical properties. Hence an investigation was conducted on various soaking time (0, 12, 24 and 48 hours) during fiber treatment using 6% concentration of sodium hydroxide (NaOH).  Two types of composite panels were then prepared which consisted of 20 wt% untreated and treated kenaf fibers with fiber size in the range of 150 – 300 micron and 350 -500 micron.   The Tensile,  Flexural and Fracture tests were then performed on the composite specimens according to ASTM D3039, ASTM D790 and ASTM E399 respectively. Scanning Electron Microscope (SEM) was used to observe the morphological surface of kenaf fibers and its composites.  The investigation showed that 24 hours is the best soaking time for 6% NaOH concentration for both kenaf size range of 150 – 300 mm and 350-500 µm.   The highest improvement is up to 59% and 71% of tensile and flexural strengths, achieved by 150 - 300 mm kenaf/epoxy composite, meanwhile 95% and 60% improvement for tensile modulus and flexural modulus for the same kenaf size.  The fracture toughness has also showed enhancement of 69% upon 24 hours soaking time.